Understanding the Development of Wuchang Eighteen Martial Arts: A Procedural Grounded Theory Study - Chen, Wenyao; Shapie, Muhamad Nizam Mohamad; Rahim, Mohamad Rahizam Bin Abdul (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Background and aim. Traditional martial arts practices develop through social processes within communities and continually interact with changes in the broader social environment. In this context, the Wuchang Eighteen Martial Arts, rooted in the Wuchang community of Hangzhou, demonstrates the dynamics of development shaped by the inheritance of traditions, social relations, and the configuration of cultural arenas. Using a procedural grounded theory approach, this study examines and explains the development process of the Wuchang Eighteen Martial Arts as a contextually and process-based cultural practice.Methods. This study employed a qualitative approach with a procedural grounded theory design. The subjects were selected based on their direct involvement, experience, and knowledge of the Wuchang Eighteen Martial Arts practice. They included five traditional inheritors, active practitioners, community leaders, and cultural administrators. Data were collected through literature review, oral history interviews, and field observations. Data analysis was conducted systematically through open coding, axial coding, and selective coding, applying constant comparative analysis until theoretical saturation was achieved.Results. The research identified three core categories that shaped the development of Wuchang Eighteen Martial Arts: habit, field, and cultural capital. Habit represents internalized habits and practices that support cross-generational transmission. Field represents the dynamic social arena where martial arts practices are negotiated within community, institutional, and public exchange spaces. Cultural capital encompasses embodied skills, symbolic authority, and institutional recognition that provide legitimacy and sustainability to the practice.Conclusions. This study demonstrates that the development of Wuchang Eighteen Martial Arts is a relational and process-based phenomenon shaped by the interaction between habit, field, and cultural capital. These findings enrich the study of traditional martial arts as a living cultural practice while providing theoretical contributions through the application of a procedural grounded theory approach in understanding the dynamics of cultural practices, and offer a process-based analytical framework relevant for further research and future strategies for preserving intangible cultural heritage.